2021
DOI: 10.1016/j.clineuro.2020.106324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression on gait variability in Parkinson’s disease

Abstract: The goal of this study was to analyze how depression associated with Parkinson's disease (PD) affected gait variability in these patients using a dual-task paradigm. Additionally, the dependency of the executive functions and the impact of depression on gait variability were analyzed. Patients and Methods: Three subject groups were included: patients with PD, but no depression (PD-NonDep; 14 patients), patients with both PD and depression (PD-Dep; 16 patients) and healthy controls (HC; 15 subjects). Gait was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Based on findings from the current study, emotional states did not influence gait variability, nor postural control. Previous research showed that different mood disorders, namely increased anxiety in older adults with PD showed greater step-to-step variability [19] and depression was shown to impact swing time variability (although this exists in the pace domain according to the 5-factor model of gait) [12]. The sample in this study involved young healthy adults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on findings from the current study, emotional states did not influence gait variability, nor postural control. Previous research showed that different mood disorders, namely increased anxiety in older adults with PD showed greater step-to-step variability [19] and depression was shown to impact swing time variability (although this exists in the pace domain according to the 5-factor model of gait) [12]. The sample in this study involved young healthy adults.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas other emotional states such as sadness and fear feature a reduction in speed, stride length, and step count [8][9][10]. Much of this past work has focused on quantifying aspects of pace, rather than variability of gait even though recent research has emphasized the clinical relevance of gait variability [11,12]. Furthermore, it is also important to note that most of the previous studies used a sample of professional actors to quantify emotional differences in walking, which can bias or exaggerate effect size of the results given that skilled actors are highly trained to produce stereotyped expressions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Pharmacological interventions treating other PD symptoms, such as depression (eg, serotonergic drugs), or interventions targeting other neurotransmitter systems, such as the noradrenergic system, could provide prognostic insights as these have had some effects on freezing and mobility deficits in PD. [55][56][57][58] The model-based predictions were tested for their usefulness in clinical trial enrichment scenarios. Enriching trial enrollment for participants that are more likely to reach an endpoint of interest has been used in other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study has limitations. While in part our findings could be attributed to depression which was shown to affect gait parameters, in particular swing time variability [ 27 ], we excluded patients with major depression, and, while depressive symptoms have worsened over follow up, overall Hamilton depression rating scale score remained well below proposed threshold for depression (5.02 ± 4.40 vs. 7.02 ± 5.85; p = 0.022). Additionally, we did not take into account weight changes nor level of exercise as potential factors that could had had some impact on our findings.…”
Section: Discussionmentioning
confidence: 99%